How can a top-down government program can be sustainable: A case study of horticulture village program in South Sulawesi Province - Valeriana Darwis; Chairul Muslim; Lyli Mufidah; Retna Qomariah; Yanti R. Darsani; Suharyon; Adri; Firdaus; Viktor Siagian; Juni Hestina; Saptana; Ashari; et al. (PLoS ONE, 2025)
The horticulture village program is one of the activities in increasing sustainable vegetable production. The activity was carried out in 2021 and one of the provinces that carried it out was the province of South Sulawesi. The purpose of the paper is to evaluate the sustainability of the horticulture village program from four dimensions, namely input, process, product, context/outcome, using the Rapfish analysis tool, and strengthened by partial budget analysis to see the magnitude of changes in revenue. From the results of the Rapfish analysis, it could be seen that horticultural village activities are less sustainable, with the lowest value in the product dimension. The main reason for this is that the planning and implementation of the program lacked a well-thought-out social process. It requires the need for improvement in terms of quantity and quality of seeds, which considers the suitability and habits of farmers. Assistance from extension workers related to the use of appropriate and periodic technology for plant conditions (product) which will have an impact on productivity and income (context) needs to be considered. The increase in income for chili and shallots due to following the recommendations of cultivation technology, including reducing the use of chemical fertilizers, increasing the use of organic fertilizers, reducing the use of chemical pesticides and using plastic mulch, can be an entry point to convince farmers of the sustainability of this program with further improvements.